Changes in early adolescents' time use after acquiring their first mobile phone. An empirical test of the displacement hypothesis - Röhlke, Leo (University of Bern, Department of Social Sciences, 2024)
This study empirically tests the displacement hypothesis, examining whether adolescents' mobile phone use displaces time spent on activities that benefit cognitive development and academic performance. Longitudinal time-use data from a sample of Australian early adolescents (ages 10-13) and a difference-in-differences design are used to model the effect of first mobile phone acquisition on allocation of time to various activities. The results challenge the displacement hypothesis, providing no evidence that mobile phone acquisition displaces enrichment, physical activity or sleep time in early adolescence. However, acquiring a mobile phone is associated with a significant reduction in time spent watching TV, movies, or videos. This suggests the rise in adolescent mobile phone use may partly represent shifting away from traditional screen activities rather than displacing cognitively beneficial activities. Guidelines for parents recommending later ages of mobile phone acquisition are unlikely to affect early adolescents' time spent on non-screen activities.
University of Bern Social Sciences Working Papers 49
Keywords: Adolescents and youth; Childhood and child development; Families and relationships; Learning, education and training; Lifestyle